"Ah, I know why…": children developing understandings through engaging with a picture book. (27th March 2015) - Braid, Christine; Finch, Brian
Abstract: This article describes part of a study that explored the responses of nine‐ and ten‐year‐old children during a picturebook read aloud in a small group setting in a New Zealand classroom. The read aloud was interactive, where the participants were encouraged to respond to the book and to each other throughout the session. The authors created a framework for analysing the responses, adapting the model of Lawrence Sipe (2008) with its five categories of literary understanding, by expanding on the analytical category to enable a finer analysis of the responses. This article discusses the children's depth of thinking and the understandings they developed as they engaged with the read aloud. It also describes how the adapted framework allowed a closer analysis of these understandings, including the way the elements of art used in the illustrations contributed to the children's ideas. The findings suggest ways picturebooks can be used to promote children's thinking and how teachers can guide discussion about a complex text. Implications for use of the framework in further research are discussed.